2018
DOI: 10.1080/19420862.2018.1532766
|View full text |Cite
|
Sign up to set email alerts
|

The first World Health Organization International Standard for infliximab products: A step towards maintaining harmonized biological activity

Abstract: Due to the increase in the number of infliximab products, the need for global harmonization of the bioactivity of this monoclonal antibody was recognized by the World Health Organization (WHO). In response, the National Institute for Biological Standards and Control (NIBSC) developed the first international standard (IS) for infliximab, which targets tumour necrosis factor (TNF). Each ampoule is assigned values of 500 IU of TNF neutralizing activity and 500 IU of binding activity. Two preparations of inflixima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…A prospective study—using the same assay as our centre—showed median subtherapeutic IFX trough level of 0.9 ug/mL in 138 CD patients . Another study reported that 52% of their IBD cohort had subtherapeutic IFX levels, though using a lower threshold of <2 µg/mL Assays can vary in their detection of IFX levels but this disparity should improve with the recent introduction of an international standard …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A prospective study—using the same assay as our centre—showed median subtherapeutic IFX trough level of 0.9 ug/mL in 138 CD patients . Another study reported that 52% of their IBD cohort had subtherapeutic IFX levels, though using a lower threshold of <2 µg/mL Assays can vary in their detection of IFX levels but this disparity should improve with the recent introduction of an international standard …”
Section: Discussionmentioning
confidence: 77%
“…24 Another study reported that 52% of their IBD cohort had subtherapeutic IFX levels, 25 though using a lower threshold of <2 µg/mL Assays can vary in their detection of IFX levels 26 but this disparity should improve with the recent introduction of an international standard. 27 We have also described here the late development of ATI. The risk of antibody development seems to be present throughout treatment with IFX but is highest in the first 12 months of treatment with nearly 80% of patients developed ATI during this period.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, the WHO has prepared two international standards for the two anti-TNF-α biologics, etanercept and infliximab. These have been tested by several laboratories within an international collaborative study using a number of different cell-based assays [12,13]. In this chapter, we have presented an overview of the most routinely used tests for potency testing of anti-TNF-α biologics, which measure in vitro responses of nonmanipulated or genetically engineered human and animal cell lines, with various readout systems.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 contains some basic information regarding the most frequently used routine TNF-α neutralization (A), ADCC (B), and CDC (C) tests. The majority of data on bioassays presented in Table 1 (see next page) were summarized from two publications describing the establishment of the first infliximab and etanercept World Health Organization (WHO) International Standards [12,13]. These were performed within international collaborative studies, confirming their high degree of relevance and analytical laboratory utility.…”
Section: In Vitro Cell-based Bioassays For General Potency Assessmentmentioning
confidence: 99%
“…This aberrant response may be as a result of a reduction in commensal bacteria and an increase in potentially pathogenic bacteria [ 3 ]. Most of the treatments developed for IBD use small molecules, vaccines, anti-TNF, or monoclonal antibodies to modulate the immune response in the gut [ 4 , 5 , 6 ]. Unfortunately, these therapies fail for a third of patients, most likely because of the complexity of the disease and the suggested imbalance of the gut microbiota [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%